A review: Surface plasmon resonance-based biosensor for early screening of sars-cov2 infection - Syed Nor, Sharifah Norsyahindah (Institute of Electrical and Electronics Engineers, 2022)
Rapid viral diagnosis is essential to contain the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) in the community and ensure effective patient management. However, the current gold standard for diagnosis of viral disease depends on the time-consuming molecular technique. Surface plasmon resonance (SPR) phenomenon has been widely applied in the analysis of biomolecular interactions and analytes detection, which is currently being investigated as a quick diagnostic method of numerous viral infections. In this regard, researchers have performed experimental studies dedicated to enhancing the sensitivity and specificity of the SPR sensor performance for utilization in the medical diagnostic field. In this review, we summarized various SPR application including the recent advancements and advantages of different types of SPR-based biosensor such prism-based, localized surface plasmon resonance (LSPR), fiber optic, optical grating, and optical waveguide for the detection of SARS-CoV2. We proposed various technical recommendations to improve the sensitivity, accuracy, time response, and cost-saving means of the SPR sensor. A special focus was set for sensitivity enhancement aspects in terms of the type of prism, nanomaterials, support layer with type and shape of optical fibers for early, swift, and ultra-sensitive detection of viral infection. With the highlighted impacts of SPR application, this review frames the current potential and challenges of SPR in comparison to the current gold standard of viral infection diagnostic strategy.